READING RUSSIA. VOL. 3 : A History of Reading in Modern Russia (di/segni, 2020)
Scholars of Russian culture have always paid close attention to texts and their authors, but they have often forgotten about the readers. These volumes illuminate encounters between the Russians and their favorite texts, a centuries-long and continent-spanning “love story” that shaped the way people think, feel, and communicate. The fruit of thirty-one specialists’ research, Reading Russia represents the first attempt to systematically depict the evolution of reading in Russia from the eighteenth century to the present day.The third volume of Reading Russia considers more recent (and rapid) changes to reading, and focuses on two profoundly transformative moments: the Bolshevik Revolution of 1917, and the digital revolution of the 1990s. This volume investigates how the political transformations of the early twentieth century and the technological ones from the turn of the twenty-first impacted the tastes, habits, and reading practices of the Russian public. It closely observes how Russian readers adapted to and/or resisted their eras’ paradigm-shifting crises in communication and interpretation.Contributors to volume 3: Evgeny Dobrenko, Abram Reitblat, Jeffrey Brooks, Thomas Lahusen, Olga Malinovskaya, Denis Kozlov, Josephine Von Zitzewitz, Oleg Lekmanov, Catriona Kelly, Birgit Menzel, Henrike Schmidt, Birgitte Beck Pristed.